In vitro neutralization of Chlamydia trachomatis by monovalent Fab antibody specific to the major outer membrane protein. - Su, H (1991)
Monovalent Fab antibodies to serovar- and subspecies-specific epitopes of the major outer membrane protein (MOMP) of Chlamydia trachomatis neutralized infectivity for hamster kidney cells by preventing chlamydial attachment. These findings exclude the aggregation of chlamydiae as a mechanism of anti-MOMP neutralization and provide additional evidence in support of the MOMP as a chlamydial adhesin.